2004
DOI: 10.1021/ma049565w
|View full text |Cite
|
Sign up to set email alerts
|

Conformation of Cyclics and Linear Chain Polymers in Bulk by SANS

Abstract: Small-angle neutron scattering (SANS) has been used to investigate the conformation of linear and cyclic poly(dimethylsiloxane)s (PDMS) in chemically identical, undiluted blends. SANS measurements have been carried out on (1) linear hydrogenous (H) mixed with linear deuterated (D) PDMS and (2) cyclic H mixed with cyclic D PDMS. The conformational behavior of the cyclic and linear polymers is studied over a wide range of molar mass and composition. Isotopic blends of linear PDMS are shown to adopt conformations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
132
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(153 citation statements)
references
References 39 publications
(88 reference statements)
16
132
2
Order By: Relevance
“…299 Therefore, the T g s of the cyclic species were higher than those of the linear analogues for M n s < 10 kDa. These findings were in agreement with the aforementioned properties of other cyclic polymers, [62][63][64][65][66]253,274 but surprisingly the T g s of cyclic oligosiloxanes (M n s < 4 kDa) increased above T g 1.…”
Section: Bulk Propertiesmentioning
confidence: 89%
See 2 more Smart Citations
“…299 Therefore, the T g s of the cyclic species were higher than those of the linear analogues for M n s < 10 kDa. These findings were in agreement with the aforementioned properties of other cyclic polymers, [62][63][64][65][66]253,274 but surprisingly the T g s of cyclic oligosiloxanes (M n s < 4 kDa) increased above T g 1.…”
Section: Bulk Propertiesmentioning
confidence: 89%
“…299 When samples with masses above the critical entanglement molecular weight (M e ) were included, 293 the extent of entanglements was surprisingly quite similar for cyclic and linear PDMS. Information about segmental mobility and diffusion was derived from Raman spectroscopy 295 from dielectric relaxation 296,297 and from spin-spin relaxation measurements.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…With the same BFM, Suzuki et al 23 simulated ring polymers with N Ring as large as 1000 and concluded that v is bracketed by 1 / 3 Յ v Ͻ 0.365. Experimentally, at least two different values of v for ring polymers in melt have been reported: 0.42 by Arrighi et al 8 and 0.34 by Takano, 10 both from neutron scattering data.…”
Section: Introductionmentioning
confidence: 99%
“…The diffusion mechanism of rings has been suggested theoretically as amoebalike motion: they thrust and pull on unentangled loops. 1,2 For ring polymers in bulk, in spite of extensive work using experiments, [3][4][5][6][7][8][9][10] theories, [11][12][13][14] and simulations, [15][16][17][18][19][20][21][22][23] many controversies still remain.…”
Section: Introductionmentioning
confidence: 99%